Review Literature: Pengolahan Bahan Pakan Asal Crustacea Sebagai Kitin dan Kitosan: Literature Review: Processing of Feed Ingredients Derived from Crustaceans into Chitin and Chitosan - Andriani, Yuli; Tubagus Aldi Lazuardi; Angga Dwi Cahya; Aisyah (Journal of Fish Nutrition, 2025)
Chitin and chitosan are polysaccharides from the exoskeleton of crustaceans such as shrimp and crabs, chitin has several benefits if added to fish feed including functioning as a source of fiber that can improve digestion in fish, increase metabolism, and support the immune system of fish. However, with its high fiber content, chitin needs to be simplified into chitosan so that it is easier to process by the fish's digestive system, with the extraction method using chemical compounds, we can get pure chitosan that can be applied to fish feed. The purpose of this review is to determine the best dose of adding chitin or chitosan to fish feed, the method used is a descriptive method through a literature review study of various research journals. The effective dose obtained in this review is the addition of chitin around 0.04% - 8%, while for chitosan it ranges from 4% - 10%.